2016
DOI: 10.1177/1077801216663658
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-Associated Deaths in Virginia Due to Homicides, Suicides, and Accidental Overdoses Compared With Natural Causes

Abstract: This research is a case study of 309 pregnancy-associated deaths that occurred in Virginia from 1999-2005. Pregnancy-associated deaths due to homicide, suicide, or accidental overdose were compared with natural deaths. Violent deaths accounted for almost 30% of the cases. Homicides accounted for 13% of all the deaths in the sample, larger than any single natural cause of death. Homicide was the leading manner of death for Black women and was 4.5 times the rate of White decedents. Recommendations include expand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Homicide rates for ''Other'' women ranged from 0% to 3.8%. [20][21][22][23][26][27][28] Although this rate appears consistently low, homicide remains a leading cause of pregnancy-associated injury deaths in the United States. 22,26,35 Disparate numbers of missing and murdered Indigenous women 37 suggest that homicide may be responsible for more pregnancy-associated AI/AN deaths than has been recognized to date.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Homicide rates for ''Other'' women ranged from 0% to 3.8%. [20][21][22][23][26][27][28] Although this rate appears consistently low, homicide remains a leading cause of pregnancy-associated injury deaths in the United States. 22,26,35 Disparate numbers of missing and murdered Indigenous women 37 suggest that homicide may be responsible for more pregnancy-associated AI/AN deaths than has been recognized to date.…”
Section: Resultsmentioning
confidence: 99%
“…Palladino et al 26 reported that prenatal and postpartum suicide disproportionately affects AI/AN and white women, yet, others report little or no risk for AI/AN women. 20,21,[23][24][25]27 This result could be explained partially by the use of an ''Other'' race/ethnicity category; Palladino et al was the only study that reported AI/AN women as AI/AN versus ''Other. ''…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations